2021
DOI: 10.3390/cancers13194807
|View full text |Cite
|
Sign up to set email alerts
|

Cis-Acting Factors Causing Secondary Epimutations: Impact on the Risk for Cancer and Other Diseases

Abstract: Epigenetics affects gene expression and contributes to disease development by alterations known as epimutations. Hypermethylation that results in transcriptional silencing of tumor suppressor genes has been described in patients with hereditary cancers and without pathogenic variants in the coding region of cancer susceptibility genes. Although somatic promoter hypermethylation of these genes can occur in later stages of the carcinogenic process, constitutional methylation can be a crucial event during the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 155 publications
0
13
0
Order By: Relevance
“…When compared between NCKAP1 expression, tumor grade, TNM stage, and lymph node metastasis, a negative correlation was observed, suggesting that NCKAP1 may have an antitumor effect in ccRCC. Other studies have shown that transcriptional repression of tumor suppressor genes occurs with tumor progression due to hypermethylation of promoter regions ( Ruiz de la Cruz et al, 2021 ). Therefore, we speculated that low expression of NCAKP1 might be associated with high methylation levels in ccRCC, which is consistent with our previous results.…”
Section: Discussionmentioning
confidence: 99%
“…When compared between NCKAP1 expression, tumor grade, TNM stage, and lymph node metastasis, a negative correlation was observed, suggesting that NCKAP1 may have an antitumor effect in ccRCC. Other studies have shown that transcriptional repression of tumor suppressor genes occurs with tumor progression due to hypermethylation of promoter regions ( Ruiz de la Cruz et al, 2021 ). Therefore, we speculated that low expression of NCAKP1 might be associated with high methylation levels in ccRCC, which is consistent with our previous results.…”
Section: Discussionmentioning
confidence: 99%
“…These may include exposure to xenobiotic agents, alcohol, hormones, or reduced intake of DNA methylation precursors [56]. ii) High level, locus wide methylation in RAD51C, BRCA1, and POLH detected in three patients are product of noncoding genetic alterations in the neighboring regions, causing secondary cis epimutations [9,41,48]. Additional support for this hypothesis was reported recently by Takahashi et al (2023).…”
Section: Discussionmentioning
confidence: 65%
“…We propose that the hypermethylation of these promoters may be caused by neighboring mutations. This mechanism is known as cis secondary epimutation, and has been reported in colorectal cancer and other diseases [9,41,48]. Only one study of this phenomenon has been reported in HBOC patients, where an hypermethylated BRCA1 allele (>40% of promoted methylation) cosegregated with the variant c.-107A>T in the BRCA1 5'UTR [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral squamous cell carcinoma (OSCC) is the third most common cancer in developing countries and the sixth most common cancer globally [27]. Today, with the continuous development of molecular biology, it has been found that cancer was caused by genetic, metabolic, inflammatory, and epigenetic factors [28]. These lead to abnormal cell physiology and signal pathway conduction, which led to abnormal cell proliferation and differentiation, eventually developing into cancer [29].…”
Section: Discussionmentioning
confidence: 99%